THE EFFECT OF COMPANY SIZE, STOCK RETURN, AND TRADING VOLUME ON THE BID-ASK SPREAD OF STOCKS ON LQ45 COMPANIES LISTED ON THE IDX (2016-2020) - Desi Jelanti; Fitriyah (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This study aims to analyze and provide empirical evidence of the impact of business size, stock return, and stock trading volume on the bid-ask spread of stocks. This quantitative associative research uses secondary data obtained from the official website of the Indonesia Stock Exchange and the websites of each company. The population of this study is comprised of LQ45 Index companies listed on the Indonesia Stock Exchange between 2016 and 2020. The sample for this study was selected through the use of purposeful sampling, and only 70 of the provided firm data met the selection criteria. The data in this study were analyzed using panel data regression analysis and statistical EViews software. This study discovered that the bid-ask spread of a stock is influenced by three factors: the size of the company, the trading volume, and the returns on the stock. The size of the company has a significant effect on the bid-ask spread, whereas stock returns have an insignificant effect.